(untitled) (Siddhajyoti Interdisciplinary Journal, 2023)
Short and glittering phrases of brand slogans aim to create a long-lasting memory related to the brand. Because of the omnipresence of such slogans in advertising, they have substantial effects on customers. Aiming to investigate the rhetorical strategies and politics of the slogans, this qualitative study has rhetorically analyzed all 28 brand slogans of commercial banks from Nepal, employing an interpretive method. It has adopted the theoretical framework of James H. Leigh, which mainly divides rhetoric into schemes and tropes further splitting them into 41 figures of speech. The study has identified the politics of nationality, intimacy, association, place, togetherness, language, and culture through the rhetorical analysis of the selected slogans. Moreover, the leading rhetorical devices in the slogans seem to enhance the politics of association, drawing the customers’ attention with alluring music and heightening their sense of intimacy with striking, memorable, and emotional effects with the slogans. The study supports expanding the knowledge regarding rhetorical culture in marketing communication. Integrating the responses of the customers and the developers of the slogans and incorporating the slogans from various sectors in further studies may strengthen the argument related to the politics of rhetoric on brand slogans.